Prevalence and Related Factors of White Coat Hypertension and Masked Hypertension in Shunde District, Southern China - Zhu, Hailan; Zheng, Haoxiao; Liang, Xiaoyan; Huang, Chunyi; Sun, Lichang; Liu, Xiong; Qiu, Min; Mai, Weiyi; Huang, Yuli (Frontiers in Physiology, 2022)
Background: White coat hypertension (WCH) and masked hypertension (MH) can increase the risk of target organ damage. Home blood pressure monitoring is an important method for detecting WCH and MH. However, the prevalence and related factors of WCH and MH in China have been rarely reported. Objective: To explore the prevalence and related factors associated with white coat hypertension (WCH) and masked hypertension (MH) in Shunde District, Southern China. Methods: This study recruited subjects from the Physical Examination Center in Shunde Hospital, Southern Medical University. Office blood pressure and home blood pressure values were collected using the home blood pressure monitor with telemedicine device and office blood pressure monitor, and the prevalence of WCH and MH was calculated by the values. Multivariate logistic regression was used to explore the related factors for WCH and MH. Results: Four-hundred and sixty-one participants (61% male), with an average age of 49 years, were included. The prevalence of WCH and MH was 5.1 and 15.2%, respectively. Multivariate logistic regression analysis showed that smoking (OR = 4.71, 95% CI = 1.05–21.15) and family history of coronary heart disease (OR = 4.51, 95% CI = 1.08–18.93) were associated with higher odds of WCH. The associated factors for higher odds of MH were smoking (OR = 2.83, 95% CI = 1.11–7.23), family history of hypertension (OR = 2.17, 95% CI = 1.11–4.26) and family history of coronary heart disease (OR = 2.82, 95% CI = 1.07–7.45). Conclusion: WCH and MH are highly prevalent in the Physical Examination Center in Shunde Hospital, Southern Medical University. We found smoking and family history of coronary heart disease were related factors for WCH, and smoking, family history of hypertension and coronary heart disease were associated with the odds of MH. Home blood pressure monitoring with a telemedicine device should be recommended to identity abnormal BP phenotype.